Niger : Second Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Request for Modification of Performance Criteria; Staff Report; Press Release on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2009)
Niger's GDP growth is projected to decline in 2009 to 3 percent from 9.5 percent in 2008 when agricultural production reached a record level. The staff report highlights Niger's second review under the Poverty Reduction and Growth Facility and Request for Modification of Performance Criteria. The country appears relatively protected from the international downturn. Niger's economic performance has been positive in 2008 with a surge in GDP growth up to 9.5 percent from 3.3 percent in 2007.